Práticas pedagógicas de professores de história durante o Regime Militar em Santa Maria, RS, (1964-1985) - Cerezer, Osvaldo Mariotto (2002)
The objective of this thesis was to investigate, in the scope of the history of Brazilian education, how power-related relations were constructed between the Brazilian military authoritarianism in its different manifestations, such as censure, torture, political authoritarianism, and so forth, and the teaching practices of history teachers who worked in institutions of elementary and high school education in the city of Santa Maria, Rio Grande do Sul from 1964 to 1985, emphasis being given to the educational processes implanted by the successive military governments. In order to develop the research, I employed the procedures of oral history, life-history modality, as a means of methodology for the collection of data by way of remembering the past facts which became important sources of information, which have in turn come to give new directions or meanings to certain historical processes. This research project worked with teachers of history, moral and civic education (MCE), and social organization and Brazilian politics (SOBP), attempting to comprehend how power-related relations were developed between (the proponents of) military authoritarianism and the school projects carried out by these teachers in the classroom, in a period of history in which Brazilian education, particularly the discipline of history in conjunction with moral and civic education and SOBP, sought to work upon the conscience of citizens for the defense and exaltation of the armed forces, at the same time in which one sought to impede creative and critical formation pertaining to the attitudes of the government. In this sense the influences or restrictions imposed by the military governments in the teaching of history and the implications of the same for the development of teaching were investigated, as well as the implications of such restrictions on the professional and private lives of professionals of education. The military dictatorship established after the coup d’état of 1964 utilized the teaching of history and teaching work as an official means of legitimizing its acts and governmental decisions to the extent that teachers were hindered from carrying out any creative or critical work in history, and simultaneously were obligated to follow the programs of the official teacher’s manuals of the time, which corresponded to the ideology of the group in power. Considering the great limitation that history, MCE, and SOBP teachers found in the development of their work in the period of the military dictatorship, this study becomes necessary for a better comprehension of that period, once it has brought to present knowledge elements lived by participants who lived under the fear and insecurity of a regime which proclaimed itself to be democratic, but which in all reality, impeded any kind of critical or creative action in work done in the classroom, since the discipline of history for the group in power represented a danger to the system implanted, on approaching issues connected to power, showing a situation different from that which was defended by the power in operation.